Dance as a mental health therapy in the metaverse: exploring the therapeutic potential of dance movement therapy as a non-pharmacological treatment in the metaverse - Radanliev, P (Frontiers Media, 2024)
Introduction: This study conducts a detailed qualitative review of Alternative Therapies for mental health and proposes a novel design for integrating Non-Pharmacological Interventions into the Metaverse Extended Reality environments. Aim/Question: This study investigates the potential of the Extended Reality environments for Non-Pharmacological Interventions in Mental Health, with a specific focus on Dance Movement Therapy as a preventive and therapeutic strategy for anxiety, depression, and other mental health conditions. Method: This study conducts qualitative evidence syntheses of primary quantitative data and performs meta-analyses of existing studies of participants reporting anxiety, depression, or other mental health conditions. Results: Dance Movement Therapy in the extended reality environments shows promise as a viable alternative therapy, but data privacy and ethical considerations must be addressed. Discussion: This study raises significant concerns regarding the privacy and security of participants' data, necessitating the storage of only the metadata in electronically compatible files, in cases where users' data is stored for long-term preservation. Implications for Practice: The outcomes of this study could revolutionize mental health practice, providing effective Non-Pharmacological Interventions for anxiety, depression, and other mental health conditions.